2021
DOI: 10.52728/ijjm.v2i3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Marketing Innovation Mediation on The Influence of Organizational Creativity on Marketing Performance During The Covid-19 Pandemic Study on MSMEs Incorporated in Bojonegoro APMMIK

Abstract: This study aims to determine the effect of organizational creativity on marketing performance mediated by marketing innovations in MSMEs who are members of APMMIK Bojonegoro during the pandemic. The respondents used were 103 MSMEs owners, the test was carried out using the variant-based Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the smartPLS 2.0 M3 program. Based on the results of the analysis, it can be concluded that organizational creativity has a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The results of the analysis of market orientation, product innovation and creativity partially and simultaneously influence marketing performance in MSMEs (Methasari, Kurniawan, & Sidik, 2018). Organizational creativity has a positive and significant effect on marketing innovation, marketing innovation has a positive and significant effect on marketing performance, and organizational creativity has a negative and insignificant effect on marketing performance in MSMEs (Wijayanto & Sanaji, 2021). Creativity and product innovation simultaneously have a positive and significant influence on MSMEs business performance (Kalil & Aenurohman, 2020).…”
Section: Increase In Sales Volume/income Turnovermentioning
confidence: 99%
“…The results of the analysis of market orientation, product innovation and creativity partially and simultaneously influence marketing performance in MSMEs (Methasari, Kurniawan, & Sidik, 2018). Organizational creativity has a positive and significant effect on marketing innovation, marketing innovation has a positive and significant effect on marketing performance, and organizational creativity has a negative and insignificant effect on marketing performance in MSMEs (Wijayanto & Sanaji, 2021). Creativity and product innovation simultaneously have a positive and significant influence on MSMEs business performance (Kalil & Aenurohman, 2020).…”
Section: Increase In Sales Volume/income Turnovermentioning
confidence: 99%
“…According to (Wijayanto & Sanaji, 2021), a feasibility study is an evaluation and analysis of the potential of a proposed project and is based on research to provide a complete analysis to minimize the risks that will be faced so as to provide full comfort to the entrepreneur's decision to continue the project.…”
Section: Framework Theorymentioning
confidence: 99%
“…Feasibility studies aim to provide project-specific decisions with comprehensive information to decide whether a business project is economically profitable. There are 5 (five) purposes why it is necessary to conduct a feasibility study before a business or project is carried out: (Wijayanto & Sanaji, 2021) Implementation of Human Resources Scorecard-Based Human Resources Work System Design at PT. Suryasukses Abadi Prima Septiani and Setiadi a) Avoid The Risk of Loss, there is a condition of uncertainty that cannot be predicted to occur or occur by itself, so that the feasibility study serves to minimize these unwanted risks.…”
Section: Framework Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results pertaining to innovation and its impact on BP are still mixed (Apanasovich et al, 2017;Hu et al, 2020;Alakrash et al, 2022). For this reason, several studies suggested the need to include MI to understand its effect on performance (Saunila, 2020;Siriram, 2022) or the variables that can affect MI (Yuliana & Kristiana, 2021). This study focuses on SMEs in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%